2018
DOI: 10.1007/s00520-018-4499-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer support on health-related quality of life in recently diagnosed breast cancer patients: a randomized controlled trial

Abstract: PurposeBreast cancer is the most common cancer of Finnish women. Peer support could be a way to help breast cancer patients to deal with the disease but studies on its effectiveness have produced conflicting results. The aim of this randomized controlled trial was to study the effectiveness of peer support on health-related quality of life (HRQoL) of breast cancer patients.MethodsPatients with recently diagnosed breast cancer at the Helsinki University Hospital were randomly allocated to intervention (n = 130)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
0
36
0
2
Order By: Relevance
“…These variable findings suggest the content and structure of the group sessions may impact the psychological outcomes of participants, and thus further research is needed to evaluate the design and implementation of these interventions. Randomized trials evaluating the impact of peer support on the quality of life of breast cancer patients have similarly identified variability in peer selection and implementation of the peer support program as contributing to the variability in their findings [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variable findings suggest the content and structure of the group sessions may impact the psychological outcomes of participants, and thus further research is needed to evaluate the design and implementation of these interventions. Randomized trials evaluating the impact of peer support on the quality of life of breast cancer patients have similarly identified variability in peer selection and implementation of the peer support program as contributing to the variability in their findings [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, in a study by Toija et al, after treatment of breast cancer (without chest wall resection and reconstruction), the mean 15D HRQoL score was 0.886. 24 Rautalin et al found that the mean 15D HRQoL score after treatment of breast cancer is 0.91. 25 The present study found relatively similar results of mean 15D score of 0.88 among patients who underwent chest wall resection and reconstruction due to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, high scores indicate a higher quality of marital life [19]. Also, the internal consistency of the whole questionnaire using Cronbach's alpha coefficient in other countries was reported to be 0.86 [20]. In this study, to investigate the internal consistency reliability of the questionnaire using Cronbach's alpha, the coefficients for marital agreement, marital satisfaction, marital cohesion, and whole questionnaire were 0.81, 0.80, 0.74, and 0.87, respectively.…”
Section: Marital Quality Of Life Questionnairementioning
confidence: 97%